Impact of steroid withdrawal on subclinical graft injury after liver transplantation: A propensity score-matched cohort analysis - Campos-Murguia, Alejandro; Bosselmann, Emily A.; Hartleben, Björn; Wedemeyer, Heiner; Engel, Bastian; Taubert, Richard; Jaeckel, Elmar (Frontiers in Transplantation, 2023)
Subclinical graft injuries in orthotopic liver transplantation may threaten long-term graft survival and could be the result of chronic under-immunosuppression. It is not known whether steroid withdrawal increases the risk of subclinical immune responses against the graft. This retrospective single-center study aimed to assess the risk of subclinical graft damage after steroid withdrawal within the first nine months after orthotopic liver transplantation in the first three years after transplantation in a prospective cohort of surveillance biopsies using a propensity score matching analysis. Of 355 patients, 109 patients underwent surveillance biopsies between eleven and 36 months after liver transplantation. Thirty-seven patients discontinue steroids within the first nine months and 72 later than nine months after transplantation. The matching led to 28 patients per group. Patients with autoimmune hepatitis, primary biliary cholangitis, and hepatocarcinoma were excluded by the propensity score matching unintentionally. Patients who discontinued steroids had a trend toward lower levels of immunosuppression at the time of surveillance biopsy. Steroid withdrawal in the first nine months was not associated with an increased risk of subclinical T cell-mediated rejection, graft inflammation, or liver graft fibrosis in the matched cohort with patients with a low frequency of autoimmune liver diseases. There were also no differences in the development of metabolic diseases. In conclusion, steroid withdrawal within the first nine months after transplantation, as assessed by surveillance biopsies, does not increase the risk of subclinical graft injuries or fibrosis at least in liver transplant recipient without or a low prevalence of autoimmune liver diseases.